ON THE INTERACTION BETWEEN TENSE AND COMP IN SPANISH: EVIDENCE FROM MATRIX, EMBEDDED, AND ATB WH-EXTRACTION - 颯楊(Gerardo Fernández-Salgueiro) (Taiwan Journal of Linguistics, 2020)
In this paper I examine the relation between Tense and Comp in Spanish. While it is well established that matrix questions in English display T-to-C movement except in the case of subject wh-questions, the analysis in the case of Spanish is far from clear (see, e.g., Torrego 1984, Suñer 1994, Gallego 2007). I first discuss how data from Across-The-Board extraction present problems for a T-to-C movement analysis. As shown in Fernández-Salgueiro (2008), ATB extraction in Spanish need not display the same Tense interpretation in all conjuncts, which I argue is unexpected if T-to-C movement occurs. In order to account for this parametric difference, I argue that interrogative C is affixal and needs to lower and attach to T. This analysis will also account for certain other word order restrictions found in the language. I also explore the consequences of this analysis for a number of other phenomena including embedded wh-questions, exclamative sentences, and more specific cases of word order variation.